Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3892/mmr.2017.6382
|View full text |Cite
|
Sign up to set email alerts
|

Lead exposure and plasma mRNA expression in ERBB2 gene

Abstract: Epidemiologic data for carcinogenicity in those exposed to lead (Pb) suggests relations with cancers although the totality of the evidence is inconsistent. Alterations in the expression of ERBB receptors have been studied during the development and malignant transformation of different kinds of human tumors where they induce proliferation, angiogenesis and metastasis generation. Relevant clinical data demonstrate the role of ERBB2 receptors in the development and malignancy of human cancers. Therefore, the obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Metals present in air, water, and food may impact human health [30,31,32,33,34,35,36,37,38]. Some metals are essential (chromium, iron, copper, magnesium, and zinc), but at high concentration may be toxic, while others metals do not play any specific role in biological processes (aluminum, nickel, cadmium, mercury, and lead).…”
Section: Chemical Pollutantsmentioning
confidence: 99%
“…Metals present in air, water, and food may impact human health [30,31,32,33,34,35,36,37,38]. Some metals are essential (chromium, iron, copper, magnesium, and zinc), but at high concentration may be toxic, while others metals do not play any specific role in biological processes (aluminum, nickel, cadmium, mercury, and lead).…”
Section: Chemical Pollutantsmentioning
confidence: 99%
“…ERBB2 is a member of the EGFR family, which consists of four members (EGFR, ERBB2, ERBB3, and ERBB4) that act as tyrosine kinase receptors. Ferrante et al (2017) indicated the association between plasma mRNA expression in ERBB2 gene and BLL (16.07 ± 6.74 µg/dl) in a healthy population. However, the authors emphasized that the impact of Pb on ERBB2 receptors is still less understood.…”
Section: Discussionmentioning
confidence: 91%
“…Apart from the above mentioned mechanisms, some carcinogens not only affect DNA directly but also can lead to cancer development in other ways. A recent study suggests the possible impact of Pb on ERBB-2 Receptor Tyrosine Kinase 2 (ERBB2) expression (Ferrante et al, 2017). Alterations in the expression of ERBB receptors were associated with transformation of different types of human tumors in which they induce proliferation, angiogenesis, and metastasis generation (Tome-Garcia et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the machinery by which plasticizers alter the epigenetic assets of cells require further study to elucidate the biology and biochemistry relatively to epigenetic alterations but also to disease-associated epigenetic alterations. A better understanding of these mechanisms will lead to better prediction of the health effects of plasticizers, allowing more targeted, easy, and appropriate disease-prevention and therapy strategies [49,50].…”
Section: Discussionmentioning
confidence: 99%